Variations in salinity tolerance of malaria vectors of the Anopheles subpictus complex in Sri Lanka and the implications for malaria transmission - Surendran, S.N.; Jude, P.J.; Ramasamy, R. (Bio Med Central, 2011)
Background: Anopheles subpictus sensu lato, a widespread vector of malaria in Asia, is reportedly composed of four sibling species A-D based on distinct cytogenetic and morphological characteristics. However An. subpictus species B specimens in Sri Lanka are termed An. subpictus B/ An. sundaicus because of recent genetic data. Differences in salinity tolerance and coastal/inland prevalence of An. subpictus sibling species that were not previously established in Sri Lanka are presented here. Results: Specimens with morphological characteristics of all four Indian An. subpictus sibling species were found in Sri Lanka. Sibling species A, C and D tended to be predominant in inland, and An. subpictus species B/An. sundaicus, in coastal localities. Sibling species C was predominant in both adult and larval inland collections. Larvae of An. subpictus B/An. sundaicus were found in inland and coastal sites, including a lagoon, with salinity varying from 0 to 30 ppt. An. subpictus sibling species A, C and D larvae were present in water of salinity between 0 to 4 ppt. An. subpictus C, D and An. subpictus B/An. sundaicus larvae showed compatible differential salinity tolerance in laboratory tests. The first instar larvae of An. subpictus B/An. sundaicus showed 100% survival up to 15 ppt in comparison to species C and D where the corresponding values were 3 ppt and 6 ppt respectively. However all third instar larvae of An. subpictus B/An. sundaicus survived up to 30 ppt salinity whereas An. subpictus C and D tolerated up to 4 ppt and 8 ppt salinity respectively. Conclusions: The results suggest that An. subpictus species B/An. sundaicus breed in fresh, brackish and nearly saline water while An. subpictus species C and D do so in fresh and less brackish waters in Sri Lanka, as in India. Because of the established role of An. sundaicus s.l. and An. subpictus s.l. as malaria vectors, the findings indicate a need for greater monitoring of brackish water breeding habitats in Asia. Tolerance to 15 ppt salinity may also constitute a simple method for differentiating An. subpictus B/An. sundaicus larvae from those of An. subpictus species C and D in field studies.